Genetic Engineering of Phenylpropanoid Pathway in Leucaena leucocephala - Khan, Bashir M.; Rawal, Shuban K.; Arha, Manish; Gupta, Sushim K.; Srivastava, Sameer; Shaik, Noor M.; Yadav, Arun K.; Kulkarni, Pallavi S.; Abhilash, O. U.; SantoshKumar; Omer, Sumita; Vishwakarma, Rishi K.; et al. (IntechOpen, 2012)
None